International Journal of Pediatric Endocrinology - Varma, Surendra
International Journal of Pediatric Endocrinology publishes original research, reviews, clinical studies, case reports, and editorials covering important clinical, translational, and basic research within the field of pediatric endocrinology. The journal is particularly interested in topics including growth conditions and the affecting factors such as diet and supplementation;  hormone action, effects and therapies; glycemic control; diabetes and genetic markers and therapy.